ISLAM NUSANTARA MENURUT NAHDLATUL ULAMA - Anggun Kurnia Robbani Rosita (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
Islam Nusantara is very important to recognize Islamic identity in Indonesia and strengthen harmony and tolerance between religions. Nahdlatul Ulama (NU), the largest Islamic organization in Indonesia, has a unique view of Indonesian Islam, which combines the values of tolerance, tawazun and justice, and emphasizes the harmonization of Islamic values with local wisdom. Islam Nusantara shows Islam's ability to adapt to local culture without sacrificing the essence of its teachings and plays a role in creating a harmonious and tolerant environment. In the era of globalization, Islam Nusantara provides a model for adapting Islam that maintains local identity and oflers a moderate and inclusive approach as an anti-extremist ideology. The focus of this research is on NU because of its great influence in Indonesia, its moderate and inclusive approach, and its long history of integrating Islamic values with local wisdom. This research aims to understand the importance of Islam Nusantara for NU and its impact on social, national and state life, as well as its contribution in strengthening the values of moderation and pluralism in Indonesia.